Метанаратив М.Грушевського в історіографічному дискурсі доби Модерну - Тельвак, В. (Інститут історії України НАН України, 2008)
The article is devoted to the analysis of the discussions about M.Hrushevsky‘s views in Ukrainian, Russian, Polish, Czech and largest – West European historiography. The social -political and ideological context of given notes, their dependence on the changing of the situation in Eastern European region on the eve of the First World War has been outlined. The conclusions about influences of this discussion on the modernization of the theoretic methodological bases of the Ukrainian historiography in the beginning of the XX-th century have been made.